2021
DOI: 10.3390/polym13203502
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison among Lignin Modification Methods on the Properties of Lignin–Phenol–Formaldehyde Resin as Wood Adhesive

Abstract: The research aim of this work is to determine the influence of lignin modification methods on lignin–phenol–formaldehyde (LPF) adhesive properties. Thus, glyoxal (G), phenol (P), ionic liquid (IL), and maleic anhydride (MA) were used to modify lignin. The modified lignins were used for phenol substitution (50 wt%) in phenol–formaldehyde adhesives. The prepared resins were then used for the preparation of wood particleboard. These LPF resins were characterized physicochemically, namely by using standard methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…However, Younesi-Kordkheili and Pizzi [ 22 ], comparing modification methods on the properties of lignin-phenol-formaldehyde resin, achieved almost the same density values, namely around 1220 kg·m −3 . However, the solid content of the produced resins was higher at 60%.…”
Section: Resultsmentioning
confidence: 99%
“…However, Younesi-Kordkheili and Pizzi [ 22 ], comparing modification methods on the properties of lignin-phenol-formaldehyde resin, achieved almost the same density values, namely around 1220 kg·m −3 . However, the solid content of the produced resins was higher at 60%.…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, the focus of most lignin applications has been on its use as a raw material, depolymerized, or functionalized polymer. In fact, unmodified and modified lignin has been widely used in wood-adhesive materials, 6,23 composites, 24,25 biomedical products, 2,26 flame retardants 27,28 and bio-adsorption applications. 29,30 Still, the implementation of lignin in catalysis is to date rarely introduced due to its complex structure and heterogeneous properties, with only relatively few studies devoted to extending the values of lignin in catalysts as a support or functional polymer in certain catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the influence of some modification methods were investigated regarding the adhesion properties of lignin-phenol-formaldehyde resin, and this study concluded that, regardless the modification method, the use of lignin to replace phenol effectively improves the gluing performance. Lignin was extracted in laboratory using a synthesis with duration of 240 min [ 18 ]. Despite the knowledge on lignin on different aspects related to potential of use, structure and modification, further studies are required to understand practical issues associated to the intrinsic variability of lignin from different sources or processes, and the respective improvement processes for industry [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Literature addressed that there are 22 lignin producers, 80% of which are focused on lignosulfonate lignin [ 16 ]. This reason justifies greater attention to the studies related to lignin from other processes, and/or extracted from black liquor and purified in laboratory conditions [ 6 , 12 , 18 , 20 , 23 ], as opposed to lignin from the Kraft pulp industry, whose extraction methods have become more efficient and commercial [ 16 ]. Thereby, it should be noted that different lignin materials present different physical and chemical properties [ 22 ].…”
Section: Introductionmentioning
confidence: 99%